Aspek Kodikologi dan Tekstologi Manuskrip Nusantara: Studi Kasus Mushaf Al-Qur’an Mbah Ismail - Magfiroh, Baiti Abir; Muttaqin, Zainal (Canonia Religia, 2024)
This article aimed to analyze the codicological and textological aspects of Mbah Ismail's Qur'an Manuscript. This paper is classified as qualitative research based on field research and applies descriptive analysis techniques with the Codicology and Textology approaches. The findings of this study are that the manuscript of the Qur'anic mushaf with inventory number 07.179 which belongs to the Mpu Tantular State Museum in terms of its codicology, this manuscript is written on daluwang paper, measuring 26 cm long, 19.5 wide and 7 cm thick and has 13 lines per page, there is illumination in the form of small flowers which are only found at the beginning of the letters al-Fatihah and al-Baqarah, written using Khat Naskhi using two red and black inks. The manuscript is bound using thread, and there is a colophon. Meanwhile, the textological aspects of this manuscript, the rasm used are rasm usmani and imla'i, regarding scholia, there are scholia maqra', juz names, hizb, text corrupt, and verse markers, In this manuscript, several corrupt (writing errors) are found, which include errors in writing letters and punctuation marks (syakl). This study has the significance of adding to the treasure of Islamic heritage through the earliest Qur'anic mushaf in the Indonesian context.